History matters, but how? An example of Ottoman and Habsburg legacies and judicial performance in Romania - Martin Mendelski; Alexander Libman (Frankfurt School of Finance & Management, 2011)
The paper examines the interdependence of historical legacies and current contextual factors as determinants of economic and political performance. It shows that behavioral patterns based on identical legacies could lead to very different (if not the opposite) results in regions with different contextual socioeconomic characteristics. Specifically, the paper compares the demand for litigation as an important aspect of judicial performance in two different historical and cultural regions of Romania, which have been in the past under indirect Ottoman rule and part of the Habsburg Empire respectively. Although Romania is currently a centralized state with common judicial system, both parts of the country inherited substantially different legacies from the history. We find that while in rich regions Habsburg legacy leads to higher demand for litigation than the Ottoman, in poor regions the situation is reversed. The results remain robust for various specifications, controls and estimation techniques.
Keywords: K41; K42; N44; O17; P26; 330; historical legacies; judicial performance; contextual factors; demand for litigation; Habsburg legacy; Ottoman legacy